Peculiarities of the functioning of the financial services market, taking into account the hypothesis of an efficient market and behavioral effects - Ivashchenko, Maryna (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2024)
Analysis and understanding of financial market principles are important for effective financial management both for individual investors and for the economy at the national and global levels. One of the key theoretical approaches to the study of financial markets is the efficient market hypothesis (EMH), according to which asset prices reflect all available information at once, so it is impossible to obtain excess profits using only public information. At the same time, the research focuses more on the influence of behavioral factors, which emphasize the role of psychological and emotional aspects in making investment decisions. The purpose of the article is to study the peculiarities of the functioning of the financial services market, taking into account the hypothesis of an efficient market and behavioral effects, as well as to identify the impact of psychological factors on investment decision-making and market dynamics. The object of research is the behavior of financial market participants. A number of research methods were used in the work on the research: analysis of scientific sources, research of historical data of the financial services market, statistical methods, quantitative analysis of behavioral effects and models of behavioral economics. The "December rally" effect has been studied and described as a phenomenon where financial markets, particularly stock markets, tend to show positive changes during December, and the January effect, when financial markets tend to show certain patterns or changes during January, the first month of the new year. The impact of the "Santa Claus Rally" effect is summarized, which describes a significant and rapid increase in market prices and indicates a rapid increase in stock indices during the New Year holidays. Statistical trends related to the day-of-the-week effect on stock exchanges have been identified, including explanations for fluctuations at the beginning of the week (Monday) and at the end of the week (Friday). The cyclicality of the stock market is described depending on the presidential elections in the country and the following years, when the stock markets show certain regularities during the four-year election cycle in the USA. Numerous cases have been identified that indicate that the financial market is also largely dependent on the actions and statements of influencers due to their influence on investor sentiment, the formation of expectations and the direct stimulation of trading activity.